A new clinical decision support tool for improving the adequacy of anticoagulant therapy and reducing the incidence of stroke in nonvalvular atrial fibrillation: A randomized clinical trial in primary care. Issue 3 (January 2018) - Dalmau Llorca, Maria Rosa; Gonçalves, Alessandra Queiroga; Forcadell Drago, Emma; Fernández-Sáez, José; Hernández Rojas, Zojaina; Pepió Vilaubí, Josep Maria; Rodríguez Cumplido, Dolores; Morral Parente, Rosa Maria; Aguilar Martín, Carina
Abstract: Introduction: Atrial fibrillation (AF) is the most common cardiac arrhythmia and increases the risk of ischemic stroke 4 to 5-fold. The first choice of anticoagulant therapy (AT) is the vitamin K antagonist (VKA). Contraindication to VKA or poor control of the International Normalized Ratio leads to the administration of direct-acting oral anticoagulants. There is a trend toward inadequate AT in nonvalvular AF (NVAF) patients. Aim: To evaluate the impact of the implementation of a decision support tool linked to the digital clinical history on the adequacy of AT, the incidence of complications, and the mortality in patients with NVAF in primary care centers (PCCs) of the Catalan Institute of Health (ICS). Methods and analysis: Randomized clinical trial in 287 PCCs, formed by 2 groups (intervention and control). Population: patients controlled in PCCs, diagnosed with NVAF 1 year before the implementation of the decision support tool and with VKA treatment over a minimum of 1 year. A simple randomization method will be performed at a sector level. The decision support tool will be available for 1 year. The time in therapeutic range (TTR) will be available in the digital clinical history only to professionals of the intervention group. The information system for primary care research development database will be used for the data extraction. Statistical analysis will be done at 3 time points: before the implementation of the tool, at 1 year, and at 2 years after the beginning of the intervention. Multilevel (patient and professional levels) logistic regression models will be used to estimate the effect of the intervention. Ethics and dissemination: This study protocol was approved by the Ethical Committee of Clinical Investigation of the Institut Universitari d'Investigació en Atenció Primària Jordi Gol (code P17/091). Articles will be published in scientific journals. Trial registration: Clinical-Trials.gov: NCT03367325.